VITAMIN C SUPPLEMENTATION IN EGG YOLK CITRATE EXTENDER OPTIMIZES BANGKOK ROOSTER SEMEN QUALITY DURING COLD STORAGE - Ananda; Faizal, Noval Jumatul; Jaswandi (BRIN - Badan Riset dan Inovasi Nasional, 2025)
This study aimed to evaluate the effect of different vitamin C concentrations (0, 0.1, 0.2, and 0.3 g/100 mL) in egg yolk citrate extender and storage time (0, 24, 48, 72, and 96 hours) on the quality of Bangkok rooster semen stored at 5°C. Using a split-plot-in-time design with four replications, semen quality was assessed for motility, viability, abnormality, intact plasma membrane (IPM), and longevity. Results showed a significant interaction (P<0.01) between vitamin C concentration and storage time on motility, and significant effects (P<0.05) on viability, abnormality, and IPM. The 0.2 g vitamin C dose preserved >40% motility and >50% viability for 96 hours and extended sperm longevity up to 11.25±0.95 days. These findings suggest that 0.2 g/100 mL vitamin C is the optimal concentration for preserving rooster semen quality during short-term cold storage.